The Impact of Artificial Intelligence in Smart City Air Purifier Systems - Alwiyah; Sayyida; Lazirkha, Diana Putri (Aptisi Transactions On Technopreneurship (ATT), 2022)
Dirty air or air pollution is one of the many natural problems that we face, the problem of harmful air pollution is very representative of a colony. If the air conditioner is not healthy so that it disturbs human health. Referring to the World Most Most Polluted Country Index, Indonesia is one of 10 countries where the air is unhealthy or polluted, requiring solutions to these natural problems. This paper aims to find solutions and minimize the impact of wider air pollution through air purification by utilizing the Artificial Intelligence mobility method, especially for outdoor areas. The problem with this system is that it provides clean air in a large area, for example, land, flats, offices, and so on, the majority of people will go out of the house and stay outside the house for a long time. Providing an intelligent sensor-based automatic drive is an advantage of this research because many air purifiers are related to the same purpose but are only explicitly made in a small room area. There are no mobility methods and no Artificial Intelligence system using the three main function formulation methods. The first formulation using "smart mobility" of the machine will be given high Artificial Intelligence. The second formulation is purification using an Arduino-based microprocessor, and the final formulation a human detector. After that, this system can be installed in residential areas and provides healthier air, referring to the structure of the formula "You Only Look Once" (YOLO). All systems will provide performance in that each function is integrated to explain the ease of this tool moves. If there is a low level of pollution, this tool will go to that place and vice versa. This tool works simultaneously, which filters air pollution & provides healthy air to humans (Artificial Intelligence). With this, the researchers tried to do several methodologies to solve air pollution outside the room and clean the dirty air to be suitable for breathing.